Professional'nyj skauting talantlivych futbolistov v Germanii - Guba, V. P.; Antipov, A. V.; Kromke, K.; Stula, A. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
In the real work features of the organization of a professional scouting of talented players on the example of the German football union are described. The Scouting allows to attract and train young football talents in mass scale. Authors refer to the number of statistical data and quotes confirming efficiency of the German system.